Metropolitan Cebu: The Challenge of Definition and Management - Ruben G. Mercado (Philippine Institute for Development Studies (PIDS), 1998)
Metro Cebu is as popular as Metro Manila. As early as 1980's, Metro Cebu has been referred to as the principal urban settlement of the Central Visayas Region. This paper attempts to present the metrowide challenges faced by Metro Cebu and discusses the issues and options for management structure that deal with these challenges
Keywords: 330; urban management; urbanization; institutional structure